A rough concrete wall-climbing robot based on grasping claws: Mechanical design, analysis and laboratory experiments. (7th October 2016) - Xu, Fengyu; Shen, Jingjin; Hu, JinLong; Jiang, GuoPing
Climbing robots have been widely used to inspect smooth walls. However, a good adsorption method has not been found for the inspection of a cliff surface and a dusty high-altitude surface with small vibration, both of which are made of coarse concrete, square brick, or rock. In this article, first, we analyzed the bionic structure of the cockroach legs and observed their morphological characteristics of the spiny claws on these legs. We also studied the interaction theory of the bionic claw with the bulges on the rough wall surfaces and deduced the mechanical criteria of the claws grabbing steadily these bulges. Then, an initial mechanical structure of a wall-climbing robot was proposed based on a grasping claw and a climbing model. Furthermore, a mathematical model was established to reflect the relationship between sharp hooks and bulges on the rough wall. Finally, we performed several laboratory experiments to verify the grasping stability.